Silverview [compact disc, unabridged] - Le Carré, John, 1931-2020 (Penguin Audio, 2021)
"Julian Lawndsley has renounced his high-flying job in the city for a simpler life running a bookshop in a small English seaside town. But only a couple of months into his new career, Julian's evening is disrupted by a visitor. Edward, a Polish émigré living in Silverview, the big house on the edge of town, seems to know a lot about Julian's family and is rather too interested in the inner workings of his modest new enterprise. When a letter turns up at the door of a spy chief in London warning him of a dangerous leak, the investigations lead him to this quiet town by the sea..."--Container.